An approximate solution of the filtration problem of a system of the dams by the finite element method - Luoc, Ngo Van; Quang, Ta Hong; Luat, Le Kim (Journal of Computer Science and Cybernetics, 2015)
Using the finite element method we construct an algorithm for solving the filtration problem of a system of dams. The program based on this algorithm is coded in FORTRAN for the EC-1022 and MINSK-32. This program is used for solving the filtration problem of Hoa Binh dam in Viet Nam.